IMPLEMENTASI SUPPLY CHAIN MANAGEMENT PADA SISTEM PENGELOLAAN BARANG DENGAN MENGGUNAKAN FRAMEWORK CI (CODE IGNITER) (STUDI KASUS BENGKEL CAHAYA MOTOR CIKIJING) - Ivan Patriana Patriana (FKOM UNIKU, 2016)
Cahaya Motor is a company engaged in repair services, sales of motor spare parts. In the process of recording sales services, repair of motor parts and reports still use simple notes into the notebook so that they are vulnerable to damage and loss of data, hence the need for a system to streamline and streamline it all. The system built closer to the concept of Supply Chain Management covering the process of purchasing goods, goods sales, motor repair services, supplier management, consumer management, returns goods, and report management. In the development of the system the author uses the Framework CI (Code Igniter). Systems built using PHP and databases using MySQL. From the built system can provide solutions for recording service purchases, sales of motor parts and motor repair has been computerized and communication media between consumers and companies become more effective and efficient